Problem dan Solusi Studi Mahasiswa Semester Tua - Raharjo, Raharjo (Nadwa, 2014)
This paper describes the problems of old-semester students in completing their study at the Faculty of Science of Islamic Education and Teaching (FITK) IAIN Walisongo Semarang. The study of exploratory qualitative approach involves 20 students from all courses taken by purposive random sampling with the tech-nique of questionnaires, interviews and documentations. The results are: (1) The problems faced by elderly semester students is a matter of academic and non-academic, namely working part time, participating organizations, teaching and unwarranted. (2) The problems are handled by the leaders of the faculty in-volved: (a) anticipatory since the beginning of their study and academic orienta-tion; (b) preventing for their study by the lecturer as supervisor; and (c) curating towards the end of the study by the head of the faculty. These steps are per-formed in order to provide opportunities for students to be able to pass and not threatened to drop out.AbstrakPaper ini menjelaskan permasalahan mahasiswa semester tua dalam menyelesaikan studinya di Fakultas Ilmu Tarbiyah dan Keguruan (FITK) IAIN Walisongo Semarang. Kajian dengan pendekatan kualitatif eksploratif ini melibatkan 20 mahasiswa dari semua program studi yang diambil secara purposive random sampling dengan teknik angket, wawancara, dokumentasi. Hasilnya adalah bahwa: (1) Mahasiswa semester tua menghadapi masalah akademik dan nonakademik berupa kuliah kerja, ikut organisasi, mengajar dan tidak beralasan. (2) Penanganan yang dilakukan pimpinan lembaga meliputi: (a) antisipatif sejak awal masa studi dan orientasi akademik; (b) preventif selama studi oleh dosen pembimbing; dan kuratif menjelang akhir studi oleh pimpinan lembaga. Langkah-langkah ini dilakukan dalam rangka memberikan peluang kepada mahasiswa agar bisa lulus dan tidak terancam drop out.